AGRICULTURE AND APPLIED STATISTICS-II - P.K. SHAHU; A.K. DAS (New Delhi Kalyani, 2007)
This book is an attempt to explain various theories of statistics which can be used in solving numerous related problems.
Index Number Series Analysis Experimental Design Stability Sustainability Multivariate Analysis
Keywords: Agriculture Statistics